2012
DOI: 10.22358/jafs/66142/2012
|View full text |Cite
|
Sign up to set email alerts
|

The effects of phytase supplementation and dietary phosphorus level on performance and on tibia ash and phosphorus contents in broilers fed maize-soyabased diets

Abstract: To test phytase efficiency, 4 dietary treatments including a positive control (T1), negative control (T2, containing 0.10% less total phosphorus than T1), negative control plus 500 FTU phytase (T3), and low-negative control plus 500 FTU phytase (T4, containing 0.13% less total phosphorus than T1) were used. Reducing the available phosphorus level of the broiler diet from 0.47% to 0.37% during the starter, and from 0.37% to 0.26% during the grower-finisher period significantly (P<0.01) depressed growth performa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 27 publications
1
5
0
Order By: Relevance
“…The phytase main effect was significant for all age periods for BWG except at 29–35 D and for FI at 0–14 D, 0–28 D, and 0–35 D, but it was not significant for FCR. Earlier investigators have shown that phytase improved live performance or was associated with a similar performance in response to adequate Ca and P i when it was supplemented in a diet with inadequate Ca and P i ( Singh et al., 2003 , Shaw et al., 2011 , Ceylan et al., 2012 ). The BWG and FI show that phytase was most effective for the first 14 D, and as the bird aged, the phytase effect was not significant.…”
Section: Resultsmentioning
confidence: 99%
“…The phytase main effect was significant for all age periods for BWG except at 29–35 D and for FI at 0–14 D, 0–28 D, and 0–35 D, but it was not significant for FCR. Earlier investigators have shown that phytase improved live performance or was associated with a similar performance in response to adequate Ca and P i when it was supplemented in a diet with inadequate Ca and P i ( Singh et al., 2003 , Shaw et al., 2011 , Ceylan et al., 2012 ). The BWG and FI show that phytase was most effective for the first 14 D, and as the bird aged, the phytase effect was not significant.…”
Section: Resultsmentioning
confidence: 99%
“…The treatments including RLL increased the disappearance of phytate phosphorus by about 16.6% more than that of the control group, which is in line with the results of Rutherfurd et al (2012), which demonstrated an increase of about 15.8%–19.3% in illegal absorption of phosphate when they used Ronozyme ® in two levels of 1,107 and 2,215 U/kg as a commercial phytase. Furthermore, application of Hostazyme ® in the low P diet decreased the excreta P content of broilers by about 16% (Ceylan, Cangir, Corduk, Grigorov, & Adabi, 2012). Additionally, an improvement in phytate disappearance in the groups fed RLL was about 12.13% higher than the chickens fed LL, indicating the phytase activity of recombinant L. lactis in the gut environment.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies indicated the positive effects of commercial phytase enzymes on tibia bone mineralization of Ca and P (Ceylan et al, 2012; Driver, Pesti, Bakalli, & Edwards, 2006; Shaw, Hess, Blake, & Ward, 2011). It was reported that the use of recombinant lactobacilli with phytase secretion potential in the broiler chickens enhances Ca and P contents in the tibia bone (Wang et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…When phytase enzyme acts on phytic acid, the availability and the utilization of these nutrients for the chicken´s increases (Sebastain et al, 1998;Ceylan et al, 2012;Cowieson, 2010). Recently, it was reported that using organic elements such as Zn, Mn, Cu and Se in broiler breeders reduced plasma triglycerides, cholesterol, LDL and VLDL (Qiujuan et al, 2012), and it was explained by the role of organic minerals in lipid metabolism by regulating lipoprotein synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…This phytic acid acts as an anti-nutritional component and, in turn, reduces the utilization of feed (Ceylan et al, 2012). Therefore, many researchers have used phytase enzyme in poultry diets, and some of them have concluded that this enzyme increases the utilization of phytic acid in poultry diets (Tiwari et al,2010).…”
Section: The Effect Of Olive Cake With or Without Enzymes Supplementmentioning
confidence: 99%